PENERAPAN BESARAN GANTI RUGI HAK ATAS TANAH YANG DIGUNAKAN UNTUK KEPENTINGAN UMUM DALAM PERSPEKTIF KEADILAN - Yuni Khairani; Putri Kemala Sari (Prodi Ilmu Hukum, Universitas Teuku Umar, 2023)
Procurement of land for development in the public interest causes turmoil in practice, where there is coercion from the parties, both the government, which sets the price of compensation unilaterally and the land owner, demands a price that is considered unfair, while the existing legal instruments have not been able to accommodate two different interests. In the end, coercion and intimidation of the community occurred in terms of land acquisition for development in the public interest. As for the purpose of this research, namely to find out the determination of the amount of compensation for land rights that are used for the public interest according to the law and to find out the determination of the amount of compensation for land rights that applies already reflects the values of justice. The research method used by researchers in conducting this research is library research or normative research. In fact, compensation for land rights used for public purposes given by the government or authorized officials to those who use the land is not entirely fair. Determination of the amount of compensation is determined based on applicable laws and regulations and other regulations as long as they do not conflict with applicable regulations. Determination of the amount of compensation also refers to the sale value of the tax object (NJOP) if there is ignorance in determining the value of compensation. Compensation given by parties who need land to landowners is unfair, there is an element of non-transparency and does not match market prices in determining the value of the compensation given. Compensation given must be in accordance with existing laws and regulations, and for people affected by land acquisition to actually receive proper compensation, which is in accordance with the results of physical measurements as well as evaluations from other aspects